Gradual ulnar lengthening in Masada type I/IIb deformity in patients with hereditary multiple osteochondromas: a retrospective study with a mean follow-up of 4.2 years - Yuchan Li; Zhigang Wang; Mu Chen; Haoqi Cai (Journal of Orthopaedic Surgery and Research, 2020)
Abstract Background Gradual ulnar lengthening is the most commonly used procedure in the treatment of Masada type I/II deformity in patients with hereditary multiple osteochondromas. However, the treatment remains controversial for the recurrence of deformity in growing children. This study aims to evaluate the clinical and radiological outcomes of ulnar gradual lengthening in our clinic. Methods We retrospectively reviewed patients who underwent ulnar lengthening by distraction osteogenesis from June 2008 to October 2017. The carrying angle (CA) and range of motion (ROM) of the forearm and elbow were clinically assessed, and the radial articular angle (RAA) and ulnar shortening (US) were radiologically assessed before lengthening, 2 months after external frame removal, and at the last follow-up. Results The current study included 15 patients (17 forearms) with a mean age of 9.4 ± 2.3 years at the index surgery. The mean follow-up period was 4.2 ± 2.4 years. There were 9 patients (10 forearms) with Masada type I deformity and 6 patients (7 forearms) with Masada type IIb deformity. The mean amount of ulnar lengthening was 4.2 ± 1.2 cm. The mean RAA improved from 37 ± 8 to 30 ± 7° initially (p = 0.005) and relapsed to 34 ± 8° at the last follow-up (p = 0.255). There was a minimal deterioration of US yet significant improvement at the last follow-up compared to pre-op (p < 0.001). At the last follow-up, the mean forearm pronation and elbow flexion increased significantly (p < 0.001 and p = 0.013, respectively), and the mean carrying angle also improved significantly (p < 0.001). No patient with type IIb deformity achieved a concentric radial head reduction. Conclusions Gradual ulnar lengthening significantly reduces cosmetic deformity and improves function in patients with Masada type I/IIb deformity. Our results supported early ulnar lengthening for patients with a tendency of dislocation of the radial head.